Motor and sport components in hierarchy of non physical culture profile pedagogic specialties students leisure - S.S. Ilchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
The research is directed at determination of non physical culture profile, pedagogic specialties 2nd-4th year students' objective preferences in choosing motor or sport functioning from admissible range of leisure kinds, offered by university or life circumstances. Purpose: to find rank place of motor and sport functioning in hierarchy of non physical culture profile, pedagogic specialties 2nd-4th year students' objective preferences in choosing motor or sport functioning from admissible range of leisure kinds. Material: in experiment 180 2nd-4th year students of Pavlo Tychyna Uman State Pedagogical University participated (90 girls and 90 boys). Results: indirectly it was found that students understand the usefulness of motor functioning and sport practicing for organism's normal functioning. It was also found that in hierarchy of leisure kinds the forms, offered by university, are not preferred by students. Sport practicing as one of leisure kinds, was preferred only by 4th year student; with it boys put it on the 1st place and girls - on the 3rd. For 2nd and 3rd year students motor and sport functioning are not significant and gave the way to other immobile forms. Conclusions: determination of motor and sport functioning rank places in students' leisure hierarchy permits to prognosticate their health related activity and direct teachers' efforts at influencing on students' understanding importance of active way of life.